PREVALENCE OF TROPICAL THEILERIOSIS IN CATTLE THROUGH BLOOD SMEAR EXAMINATION IN SUMEL DISTRICT, DUHOK PROVINCE - ISMAEL , SHAMEERAN SALMAN (Journal of Duhok University, 2023)
In Iraq, bovine theileriosis, or tropical theileriosis is a significant disease, that causes economic losses in livestock. The main causative agent is Theileria annulata. The current study was conducted from March to August of 2022 to estimate the prevalence rate of tropical theileriosis in cattle from Sumel District, Duhok Province, Kurdistan Region, and factors linked with infection.    A total of 160 blood samples were collected from cattle (with 96 females and 64 males. Thin blood films were prepared and stained with Giemsa stain, then examined under the microscope to screen morphological stages of Theileria spp. within infected red blood cells of the cattle. The results revealed a higher prevalence rate of tropical theileriosis in cattle in older females (44.38%) than in males (22.5%). Additionally, the prevalence rate of infection was higher in March (23.75%) compared to April, May, and June (13.75%, 11.87%, and 11.25%, respectively), in contrast to July and August (4.38% and 1.88%, respectively). These differences were found to be significant at a P value < 0.05. To reduce this high rate of infection and minimize economic losses in livestock an effective control method is required to reduce hard tick infestation as the primary vector for infection) and to implement regular monitoring of infections.